Study of the population dynamics of Listeria monocytogenes and Pseudomonas fluorescens in buffalo mozzarella by means of challenge testing - Donatella Nava; Salvatore Capo; Vincenzo Caligiuri; Valerio Giaccone; Loredana Biondi; Gerardo Francesco Vaccaro; Achille Guarino; Federico Capuano (Italian Journal of Food Safety, 2016)
Campania’s buffalo mozzarella is a greatly appreciated cheese in Italy and worldwide. From a microbiological standpoint, it is a highly perishable food and potentially at risk of contamination by pathogens such as Listeria monocytogenes (L. monocytogenes). The present paper reports the results of a challenge test carried out to assess the population dynamics of L. monocytogenes, alone and in presence of Pseudomonas fluorescens (P. fluorescens), in buffalo mozzarella. For this purpose buffalo mozzarella samples were contaminated with L. monocytogenes alone or combined with P. fluorescens. In samples where L. monocytogenes was inoculated alone, the bacterial load remained unchanged. On the contrary, in samples contaminated with L. monocytogenes and P. fluorescens, the growth of L. monocytogenes increased.